Content Analysis in the Research of Social Phenomena in the Organisation. Application of IRAMUTEQ Software - Glińska-Neweś, Aldona; Escher , Iwona (Studia Oeconomica Posnaniensia, 2018)
In this paper, the authors present essential problems related to content analyses, i.e. of texts obtained through qualitative research in the field of management. The main aim of the paper is to discuss opportunities given by IRAMUTEQ software for the content analyses. The software is free but still rather unknown in the Polish research community. The capabilities of the software are presented by the example of research aimed at defining the nature of positive and negative relationships in the organisation. The content being the basis for the discussion has been derived from the transcripts of individual semi-structured in-depth interviews conducted with 24 employees representing 3 companies located in and near the Polish city of Toruń. The paper presents also limitations of IRAMUTEQ usage in analysing texts created in Polish.